Association between Acute Stroke and Metabolic Syndrome–An Observational Study in a Tertiary Hospital (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Stroke is one of the leading causes of death worldwide including Bangladesh. There are various modifiable and non-modifiable risk factors for stroke. Metabolic syndrome is an important factor amongst them.Objective: To determine the association of stroke with metabolic syndrome.Materials and Methods: This cross sectional study was carried out at Neurology Centre and Family Medical Ward of combined military hospital (CMH) Dhaka from July 2018 to December 2018. Total 100 admitted cases of acute stroke (both ischaemic and haemorrhagic) were enrolled. Diagnosis was confirmed by clinical examinations, relevant laboratory investigations and CT scan and/or MRI of brain. Verbal consent was obtained from patients or next of kin. Ethical issue was addressed. Data collection was done in a prescribed form by face to face interview, clinical findings and laboratory and imaging results. Statistical analysis was carried out by using SPSS v16.0. Chi square test was done to see the level of significance.Results: Hypertension (HTN) was found in 54.6% of haemorrhagic stroke and 45.5% of ischemic stroke. Diabetes Mellitus (DM) was present in 40% of ischaemic stroke and 32% of haemorrhagic stroke. Abdominal obesity was present in 13 haemorrhagic stroke and only 4 ischaemic stroke cases. Fasting hyperglycaemia was found in 20 haemorrhagic stroke and 30 ischaemic stroke cases. Hypertriglyceridaemia was found in 33 ischaemic stroke and 18 haemorrhagic stroke cases. Low high density lipoprotein cholesterol (HDL-C) was found in 30 ischaemic stroke and 15 haemorrhagic stroke patients. Total 53 patients fulfilled the criteria of metabolic syndrome and 21 of them had 4 elements like HTN, DM, high triglyceride (TG), low HDL-C. Metabolic syndrome was present in 39 out of 54 ischaemic stroke and 14 out of 46 haemorrhagic strokes. There was significant association between metabolic syndrome and stroke especially in the ischaemic stroke (p value